EFEKTIVITAS MANAJEMEN SARANA PRASARANA DI BALAI PELATIHAN OPERASI DAN PEMASARAN AGUS SUROTO PT KERETA API INDONESIA (PERSERO) BANDUNG) - Dyah Ayu Setiani (Jurnal Tata Kelola Pendidikan, 2021)
The theme of this research is "The Effectiveness of Management Facilities at the Training Center Operations and Marketing Agus Suroto PT Kereta Api Indonesia (Persero) Bandung”. management facilities is the process of procuring and utilizing components both directly and indirectly in the education process to achieve effective and efficient educational goals. Effectiveness is reviewed by the approach of objectives, systems, constituency strategies, competitive value. The objectives of this study are 1) Obtain an overview of the effectiveness of Facilities Management in the Training Center Operations and Marketing Agus Suroto PT Kereta Api Indonesia (Persero) Bandung. 2) obtain an overview of the obstacles in the management of facilities and infrastructure at BP OPSAR PT KAI (Persero). 3) Measuring the efforts made in overcoming the strongest obstacle of managing facilities and infrastructure in the Training Center Operations and Marketing Agus Suroto PT Kereta Api Indonesia (Persero) Bandung. This study uses qualitative research because it investigates direct phenomena and describes in depth. The findings in this study are described in accordance with the research questions, namely: 1) Having an effective approach in its implementation, the organizing committee has succeeded in communicating with teachers and students in realizing effective infrastructure management goals that refer to the vision and mission of the training center. The systems approach consists of an input-process-output, monitoring and evaluation system. The strategic constituency approach is evidenced by the organizing committee and instructors who are able to meet the needs of infrastructure for the needs of stakeholders during training activities, and the training center measurement reference is to obtain accreditation certification given by the director general. The training center's competitive value approach applies modernization innovations. 2) Inhibiting factors, namely technical errors, teacher negligence in filling in the TTD and the date on the student satisfaction evaluation form, student problems, there has been no improvement in the modernization of tools in the mechanical laboratory the problem is due to illness, the committee assesses graduation with a score indicator